PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Qonita Mei Sari; Abdul Rohman (Diponegoro Journal of Accounting, 2023)
The research objective is to determine the effect of financial ratios on company financial distress with good corporate governance as a moderating variable. The population of this study is manufacturing companies in the basic industrial sector and chemicals listed on the Indonesia Stock Exchange from 2019 to 2021 with a total of 94 companies. The sample was selected by purposive sampling method. The independent variables used are financial ratios consisting of liquidity ratios, profitability ratios, leverage ratios, and activity ratios. This study uses multiple linear regression analysis to see how the independent variables affect the dependent variable. Moderation regression analysis is added to assess whether the moderating variable is able to strengthen or weaken the relationship between the independent variables and the dependent variable. The results of this study indicate that the variables of liquidity, profitability, and leverage affect the company's financial distress. While the activity variable has no effect on financial distress. In the moderation test, the results show that good corporate governance is able to moderate the effect of profitability on financial distress. Meanwhile, good corporate governance is not able to moderate the variables of liquidity, leverage, and activity on the level of financial distress. Simultaneously, all variables affect the company's financial distress.